Numerical simulation of soil–cone penetrometer interaction using discrete element method - Kotrocz, Krisztián; Mouazen, Abdul Mounem; Kerényi, György (Elsevier, 2016)
One of the most common methods to measure soil strength in-situ is cone penetrometers. In this paper the development of a three dimensional (3D) discrete element model (DEM) for the simulation of the soil–cone penetrometer interaction in a slightly cohesive loamy sand soil is presented. The aim was to investigate the effects of the soil model’s geometrical (e.g., soil model cross section shape and size and model’s height) changes on variations in the soil penetration resistance. The model area ratio and height ratio values were adopted to analyse the effects of the cross section size and the model’s height, respectively. The results of penetration resistance of the DEM simulations were compared with the in-situ measurement with a cone penetrometer of the same geometry. This comparison allowed the derivation of the contact properties between the elements. To simulate the soil material the so-called Parallel Bond and Linear Models were used in the 3D version of the Particle Flow Code (PFC) software. Finally the mechanical properties of the soil, namely the cohesion and internal friction angle were estimated by DEM simulation of direct shear box. Results showed that the penetration process can be simulated very well using the DEM. The model’s calculated penetration resistance and the corresponding in-situ measurement were in good agreement, with mean error of 14.74%. The best performing models were a rectangular model with an area ratio of 72 and a height ratio of 1.33 and a circular model with an area ratio of 32 and a height ratio of 2. The simulation output of soil material properties with direct shear box resulted in representative values of real loamy sand soils, with cohesion values range of 6.61–8.66 kPa and internal friction angle values range of 41.34–41.60°. It can be concluded that the DEM can be successfully used to simulate the interaction between soil and cone penetrometers in agricultural soils.
Keywords: Discrete element method; Cone penetrometer; Soil mechanics